(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
Voice over Internet protocol (VoIP), there is an existing way of communication over any network. The Users can make the telephone calls over an IP network using this technology. This paper will describe Voice over Internet Protocol (VoIP) to a level that allows discussion of security issues and concerns. There are two kinds of spoofing attacks are possible, first one is IP spoofing attack and another is URI spoofing attack, which are described in this review paper. The Implementation of VoIP concerned by businesses, components of a VoIP system, and relevant security issues. The business concerns will be those which are used to affect the Quality of Service (QoS). The network components call processors, gateways and two of the more common architectures are held by VoIP.